A rare sugar, allose, inhibits the development of Plasmodium parasites in the Anopheles mosquito independently of midgut microbiota - Mizushima, Daiki; Yamamoto, Daisuke S.; Tabbabi, Ahmed; Arai, Meiji; Kato, Hirotomo (Frontiers in Cellular and Infection Microbiology, 2023)
A rare sugar, allose, was reported to inhibit the development of Plasmodium parasites in Anopheles mosquitoes; however, the mechanism remains unknown. The present study addressed the inhibitory mechanism of allose on the development of the Plasmodium parasite by connecting it with bacteria involvement in the midgut. In addition, further inhibitory sugars against Plasmodium infection in mosquitoes were explored. Antibiotic-treated and antibiotic-untreated Anopheles stephensi were fed fructose with or without allose. The mosquitoes were infected with luciferase-expressing Plasmodium berghei, and parasite development was evaluated by luciferase activity. Bacterial composition analysis in gut of their mosquitoes was performed with comprehensive 16S ribosomal RNA sequencing. As the result, allose inhibited the development of oocysts in mosquitoes regardless of prior antibiotic treatment. Microbiome analysis showed that the midgut bacterial composition in mosquitoes before and after blood feeding was not affected by allose. Although allose inhibited transient growth of the midgut microbiota of mosquitoes after blood feeding, neither toxic nor inhibitory effects of allose on the dominant midgut bacteria were observed. Ookinete development in the mosquito midgut was also not affected by allose feeding. Additional 15 sugars including six monosaccharides, four polyols, and five polysaccharides were tested; however, no inhibitory effect against Plasmodium development in mosquitoes was observed. These results indicated that allose inhibits parasite development in midgut stage of the mosquito independently of midgut microbiota. Although further studies are needed, our results suggest that allose may be a useful material for the vector control of malaria as a “transmission-blocking sugar.”